Chapter Dall'idea al progetto - BIAGIOLI, RAFFAELLA (Strumenti per la didattica e la ricerca, 2022)
The Integrated Direct Digital Internship (TDDI) represented a new and important method of internship of an experimental nature (in collaboration with the Regional School Office for Tuscany) which had as its primary objective to guarantee all students the opportunity to live this fundamental pre-professional experience. The project, born almost by chance to support the condition of professional fragility caused by the pandemic, has favored the search for a new model which, through the integration of virtual methods, has expanded and enriched the training opportunities for future teachers by implementing courses unpublished. From the point of view of educational and scientific research, it was a question of experimenting, evaluating and developing differentiated professional learning practices through the comparison between innovative tools and traditional tools in order to achieve a reasoned integration.